2017
DOI: 10.1080/09513590.2017.1318276
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial flushing αVβ3 integrin, glycodelin and PGF2α levels for evaluating endometrial receptivity in women with polycystic ovary syndrome, myoma uteri and endometrioma

Abstract: The aim of this cross-sectional study is to compare endometrial flushing fluid levels of αβ integrin, glycodelin and PGF2α during the midluteal phase of the menstrual cycle of women with polycystic ovary syndrome (PCOS, n = 20), myoma uteri (n = 20) and endometrioma (n = 19) with the healthy controls (n = 20). After collecting samples at the midluteal phase of ovulatory volunteers and storing them at -80 °C, αβ integrin, glycodelin and PGF2α levels were analyzed using ELISA. The mean ages of the groups were 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
0
10
0
1
Order By: Relevance
“…That study included structural proteins and progesterone-regulated molecules. This previous study found that αVβ3 integrin and glycodelin levels were higher in the endometrioma and PGF2α was higher in the PCOS patients than the control group in a statistically significant way [12].…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…That study included structural proteins and progesterone-regulated molecules. This previous study found that αVβ3 integrin and glycodelin levels were higher in the endometrioma and PGF2α was higher in the PCOS patients than the control group in a statistically significant way [12].…”
Section: Discussionmentioning
confidence: 78%
“…In our 2017 study, we had chosen to evaluate three cell signaling molecules that have impact on endometrial receptivity with mostly paracrine effect [12]. That study included structural proteins and progesterone-regulated molecules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-and posttreatment levels of IgA, FSH and LH did not differ appreciably between the two groups, but posttreatment E2 was significantly lower in the study group. By mediating immune-inflammatory reactions, IL-6 causes local pelvic fibrosis and adhesion, and aggravates cytotoxicity, thereby promoting the development of clinical symptoms seen in endometrial women [13]. Studies have shown that TNF-α is associated with dysregulation of cytokines, and is highly expressed in endometriosis [14].…”
Section: Discussionmentioning
confidence: 99%
“…The Helsinki declaration was followed. The study was conducted with patients that were also part of another study (13). The current study focuses on the comparison of OS markers among healthy patients and patients with benign gynecological diseases, whereas the earlier study investigated endometrial receptivity marker levels of the same population.…”
Section: Methodsmentioning
confidence: 99%